UV-VIS spectroscopy characteristic of crude palm oil at 55ºC - 120ºC - Anuar, Nor Azrina (2018)
This thesis describes an application of fibre optics technique to determine properties of heated crude palm oil (CPO) at 300 to 895 nm in the ultraviolet-visible (UV-VIS) spectrum based on reflection, transmission and absorption measurement. The CPO was heated on the hotplate at 55, 80, 105 and 120 ˚C for 60 min. The heated CPO was sample out for every 10 min and let cool to room temperature before performing the measurements using an Ocean Optics USB4000 UV-VIS-NIR spectrometer. Colour of the heated CPO changed from orange-red to almost colourless particularly after 60 min suggesting that it was heat bleached. All the measurements indicated presence of tocotrienol and tocopherol, carotenoid and chlorophyll b elements at approximately 350, 460 and 650 nm, respectively. However, the measurements trend for the elements could not be determined since their variations were very small and overlapping. It was found that the reflection measurement was imprecised due to the translucency of the CPO. Conversely, the transmission and absorbance measurement were found to increase and decrease, respectively at 400 to 765 nm mainly for CPO with heating times of 50 and 60 min regardless of heating temperatures. This was probably because of change in CPO properties and its electromagnetic interaction as it had been heated for longer times. However, the transmission and absorbance for 10 to 40 min heated CPO from 55 to 105 ˚C were similar to the non-heated CPO since their colours were not much differ indicating that some of their properties and electromagnetic interaction were maintained. Region from 525 to 565 nm in the VIS spectrum was chosen for further analysis since the measurements showed many changes at these wavelengths. The cut off wavelengths from 525 to 565 nm decreased as the heating times and temperatures increased except for 105˚C which was slightly off the trend. It was possibly that the CPO was heat bleached and there was also a measurement error at 105˚C. It was also observed that the decreasing trend in the cut offs for 60 min heated CPO was different and this was probably due to change in its properties as it appeared almost colourless and had higher transparency among the CPO at other heating times. The sensitivity and critical heating time showed decreasing trends from 525 to 540 nm at all heating temperatures except for 105˚C. In addition, it was noted that the measurements were highly sensitive at low wavelengths from 525 to 540 nm and also at lower heating temperatures from 55 and 80 ˚C. The mean relative errors of the transmission and absorbance indicated that wavelengths from 540 to 555 nm and 535 to 550 nm respectively were within 10% errors for all heating temperatures excluding 105˚C. It was concluded 540 nm might be useful for the prediction of the heating times at 55, 80 and 120˚C since both measurements were highly sensitive and had mean relative error which was less than 10 % at this wavelength.